Approaches, theories, and research on creative thinking. A review study - Muñoz, César (2021)
The objective was to review the existing scientific literature of the concepts, approaches, and research carried out on creative thinking. A balance was made of the scientific works found on this type of thinking in which the three proposed axes of the study were considered. The information was obtained from sixty articles published in journals indexed to the central databases and repositories such as Ebsco, Doaj, ProQuest, Eric, and Scopus. The methodology used consisted of the systematic review of documents with scientific information. Diversity of concepts approaches and scientific studies was found in this regard that considers creative thinking as an essential capacity for the development of people in all areas of human development.